Capsaicin induced cough in cryptogenic fibrosing alveolitis. Issue 12 (1st December 2000) - Doherty, M J; Mister, R; Pearson, M G; Calverley, P M A
Abstract : BACKGROUND: Cough is a common and troublesome symptom in cryptogenic fibrosing alveolitis (CFA) but the mechanisms responsible are not known. The cough threshold to inhaled capsaicin is increased in asthma and chronic obstructive pulmonary disease (COPD) where lung volumes are increased, but the relationship between cough response and symptom intensity has not been studied in CFA where lung volumes are reduced. METHODS: Capsaicin challenge tests were performed on 15 subjects with proven CFA and 96 healthy controls. Symptoms, as assessed by daily diary card cough score and by visual analogue scale (VAS), were related to the capsaicin sensitivity (C5) and compared with lung volumes. Volume restriction was produced in a group of 12 normal healthy subjects by a plastic shell tightly strapped to the chest wall. Capsaicin challenge tests were performed in these subjects, both strapped and unstrapped, to determine whether volume restriction altered the cough reflex. RESULTS: The median C5 response in normal subjects was more than 500 μM compared with 15.6 μM in those with CFA (p<0.001). The C5 response of the CFA patients was not related to symptoms of cough (whether measured by diary card or by VAS), nor was it related to percentage predicted total lung capacity (TLC) or forced vital capacity (FVC). Volume restriction of normal subjects with chest strapping successfully restricted lung volumes to levels similar to that of the CFA patients but did not change the sensitivity to capsaicin. CONCLUSIONS: The cough reflex measured using capsaicin is markedly increased in patients with CFA. This increase is not the result of alterations in the deposition of inhaled particles of capsaicin brought about by volume restriction. It could be related to reduced lung compliance leading to sensitisation of rapidly adapting receptors, other mechanical changes, or to destruction of pulmonary C fibres secondary to interstitial inflammation. The capsaicin test may be a useful method of objectively monitoring cough propensity in CFA.